2010
DOI: 10.1039/b919583a
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of Rhodamine 6G excitation energy on cellulose microparticles

Abstract: Rhodamine 6G (R6G) was adsorbed on cellulose microparticles and fluorescence quantum yields and decays were measured as a function of dye loading. Though no spectroscopic evidence of dye aggregation was found, a noticeable decrease of quantum yield--after correction for reabsorption and reemission of fluorescence--and shortening of decays were observed at the highest loadings. These effects were attributed to the dissipation of the excitation energy by traps constituted by R6G pairs, leading to static and dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 39 publications
4
29
0
Order By: Relevance
“…At the highest loadings, concentration quenching is observed, although the aggregation tendency should be small as pointed out above. Similar results obtained for rhodamine 6G on cellulose, a system for which no aggregation could be detected spectroscopically, were attributed to excitation energy transfer and trapping (10).…”
Section: Fluorescence Spectra and Quantum Yieldssupporting
confidence: 80%
See 1 more Smart Citation
“…At the highest loadings, concentration quenching is observed, although the aggregation tendency should be small as pointed out above. Similar results obtained for rhodamine 6G on cellulose, a system for which no aggregation could be detected spectroscopically, were attributed to excitation energy transfer and trapping (10).…”
Section: Fluorescence Spectra and Quantum Yieldssupporting
confidence: 80%
“…Small amounts of water, however, strongly affect the excited state behavior of the adsorbed molecule (21). Some studies of xanthene and other dyes adsorbed on microcrystalline cellulose, such as rhodamine 6G, rhodamine 101, auramine O, rose bengal, etc., have been reported by us (10,(22)(23)(24).…”
Section: Introductionmentioning
confidence: 74%
“…shows the fluorescence spectrum of the PhG-SiO2, after being modified with aminofluorescein according to Scheme 3, with a maximum emission at 517 nm. Similar spectra have been obtained for the other fluorescent derivatives from the carboxylic NPs; small differences in peak emission (5 nm) respect to the free dye can be attributed to the change of photophysical parameters and have been observed in surface immobilized dyes (Figure ESI 5(a)) [48,49]. When the coupling reagents EDC and NHS are not present there is no fluorescence signal, pointing that the immobilization of fluorescein does not take place and we can rule out adsorption of the dye on the SiO2 surface.…”
supporting
confidence: 71%
“…Results concerning the formulation of photoactive materials obtained by our research group during the last years show that concentration quenching (CQ) precludes the achievement of efficient materials at not quite high dye concentrations. In particular, for xanthenes and similar dyes, we demonstrated that, even in the absence of spectroscopically detectable aggregation, dye pairs with molecules separated by less than 1.5 nm behave as virtual traps for the excitation energy (1). Beddard and Porter concluded long ago that, to prevent trap formation by orbital overlap, the minimum distance between chlorophyll molecules should be 1 nm when averaged over all orientations at random (2).…”
Section: Introductionmentioning
confidence: 69%